Haploinsufficiency of the genes encoding the tumor suppressor Pten predisposes zebrafish to hemangiosarcoma - Suma Choorapoikayil; Raoul V. Kuiper; Alain de Bruin; Jeroen den Hertog (The Company of Biologists, 2012)
SUMMARY PTEN is an essential tumor suppressor that antagonizes Akt/PKB signaling. The zebrafish genome encodes two Pten genes, ptena and ptenb. Here, we report that zebrafish mutants that retain a single wild-type copy of ptena or ptenb (ptena+/−ptenb−/− or ptena−/−ptenb+/−) are viable and fertile. ptena+/−ptenb−/− fish develop tumors at a relatively high incidence (10.2%) and most tumors developed close to the eye (26/30). Histopathologically, the tumor masses were associated with the retrobulbar vascular network and diagnosed as hemangiosarcomas. A single tumor was identified in 42 ptena−/−ptenb+/− fish and was also diagnosed as hemangiosarcoma. Immunohistochemistry indicated that the tumor cells in ptena+/−ptenb−/− and ptena−/−ptenb+/− fish proliferated rapidly and were of endothelial origin. Akt/PKB signaling was activated in the tumors, whereas Ptena was still detected in tumor tissue from ptena+/−ptenb−/− zebrafish. We conclude that haploinsufficiency of the genes encoding Pten predisposes to hemangiosarcoma in zebrafish.